(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Financial literacy has an effect on investment decision making by fund managers shows that a high percentage of managers consider financial concepts such as returns, investment risks, investment portfolio management and trends in interest rates at a great extend. The results indicate that in general fund managers need to be financially literate in-order to make investment decisions financial literacy skills like risks, investment portfolio, returns, and diversification of the portfolio enable fund managers to make informed investment decisions about their money and minimizes the chances of being misled on financial matters. financial literacy affects financial decision-making because individuals with low literacy are more likely to rely on other people as their main source of financial advice and are less likely to make informed investment decisions.